Entomologische Chronik (James Edward Collin F. R. E. S., Ralph Leonard Coe). - Anonym (Contributions to Entomology = Beiträge zur Entomologie, 1969)
In memoriam James Edward Collin F. R. E. S. and Ralph Leonard Coe.